2021
DOI: 10.3746/pnf.2021.26.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Can Nutrition Help in the Treatment of Infertility?

Abstract: Infertility is defined as the inability to conceive after 12 months of unprotected intercourse or six months for women aged 35 years or older. The physical, emotional, psychological, and financial statuses of infertile couples are tremendously affected especially after undergoing diagnostic and/or curative treatments. Human fertility is influenced by multiple factors including female or male, and modifiable or non-modifiable factors. There is growing evidence that nutrition may play an important role in adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 90 publications
0
19
0
2
Order By: Relevance
“…Infertility is a public health priority estimated to affect around one in six couples worldwide. Underlying medical conditions and lifestyle factors, such as smoking, diet, and exercise, have been found to be causing or contributing factors ( Chavarro et al, 2007 ; Wise et al, 2012 ; Radin et al, 2014 ; Heger et al, 2018 ; Aoun et al, 2021 ). Increasingly, studies have shown association between exposure to environmental contaminants and infertility, and among them is a particular class of chemicals that causes disturbances of the endocrine system, namely the endocrine disrupting chemicals (EDCs).…”
Section: Discussionmentioning
confidence: 99%
“…Infertility is a public health priority estimated to affect around one in six couples worldwide. Underlying medical conditions and lifestyle factors, such as smoking, diet, and exercise, have been found to be causing or contributing factors ( Chavarro et al, 2007 ; Wise et al, 2012 ; Radin et al, 2014 ; Heger et al, 2018 ; Aoun et al, 2021 ). Increasingly, studies have shown association between exposure to environmental contaminants and infertility, and among them is a particular class of chemicals that causes disturbances of the endocrine system, namely the endocrine disrupting chemicals (EDCs).…”
Section: Discussionmentioning
confidence: 99%
“…Adhesion to healthy diet, maintenance of ideal weight, and exercise may positively affect fertility for both men and women. In particular, dietary pattern, including fish, vegetables, fruits, poultry, whole grains, and healthy fats, have been related to fertility improvement and pregnancy outcome [14,84].…”
Section: Diet and Behavior Impact On Male Reproductive Healthmentioning
confidence: 99%
“…In particular, an excessive weight gained during pregnancy places the offspring at risk for metabolic, and not metabolic, diseases, probably via epigenetic mechanisms of embryo programming [13]. To contrast the adverse effect of an unhealthy diet pattern, numerous studies are aimed at disclosing the positive impact that specific food groups and nutritional supplements exert to enhance male and female reproductive functions [14].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, infertility has become a serious social, mental, and physical health problem worldwide ( 1 , 2 ). As described, infertility is a condition with multifactorial etiology, including ovulation and uterine diseases in women, as well as disrupted spermatogenesis and poor semen quality in men ( 3 ). Pathogenesis of reduced fertility and infertility includes many other factors, such as pelvic inflammatory disease, cancers, reactive oxygen species (ROS), and non-modifiable factors – age, gender, genetic, and epigenetic factors ( 1 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…As described, infertility is a condition with multifactorial etiology, including ovulation and uterine diseases in women, as well as disrupted spermatogenesis and poor semen quality in men ( 3 ). Pathogenesis of reduced fertility and infertility includes many other factors, such as pelvic inflammatory disease, cancers, reactive oxygen species (ROS), and non-modifiable factors – age, gender, genetic, and epigenetic factors ( 1 , 3 ). It is supposed that disrupted reproductive health is associated with environmental exposure to lots of chemicals, such as endocrine-disrupting chemicals (EDCs) that negatively affect endocrine homeostasis via modulation of molecular pathways involved in hormone synthesis, transport, metabolism, and hormone receptors, but also influence the hypothalamus–pituitary (HP)–gonadal axis ( 2 ).…”
Section: Introductionmentioning
confidence: 99%